2023
DOI: 10.3389/fpsyg.2023.1089264
|View full text |Cite
|
Sign up to set email alerts
|

Holding open spaces to explore beyond: Toward a different conceptualization of specialization in high-performance sport

Abstract: This conceptual analysis aims to challenge the state of high-performance sport by questioning the concept of specialization. To start, we offer a brief, but critical overview of what specialization currently entails. Then, shifting the paradigm, we suggest an expansion rather than a reduction of developmental possibilities once an athlete reaches the “top”. Specifically, rather than athletes conforming to national standards imposed by governing bodies about what it means to be “elite”, we suggest sport systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The overrepresentation of early born players is due to youth soccer organizations being embedded in a culture of growing professionalization characterized by the continuous assessment of youth players who are valued and ranked based on objective measures of performance [ 51 , 52 , 53 , 54 , 55 ]. Players’ journey within those talent pathways is often defined on their ability to meet performance standards and to fit in with the requirements of the organization [ 6 , 7 , 56 , 57 ]. Early born players experience initial benefits consisting of more time to practice, compete, and develop, which eventually provide them greater openings into talent pathways, usually supporting a faster and earlier development of sport-specific skills (i.e., short-term and immediate effects of RAEs [ 2 , 58 , 59 ] and parents’ initial enrolment bias [ 60 , 61 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The overrepresentation of early born players is due to youth soccer organizations being embedded in a culture of growing professionalization characterized by the continuous assessment of youth players who are valued and ranked based on objective measures of performance [ 51 , 52 , 53 , 54 , 55 ]. Players’ journey within those talent pathways is often defined on their ability to meet performance standards and to fit in with the requirements of the organization [ 6 , 7 , 56 , 57 ]. Early born players experience initial benefits consisting of more time to practice, compete, and develop, which eventually provide them greater openings into talent pathways, usually supporting a faster and earlier development of sport-specific skills (i.e., short-term and immediate effects of RAEs [ 2 , 58 , 59 ] and parents’ initial enrolment bias [ 60 , 61 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this research aspires to contribute to the current literature by exploring and quantifying the benefits of applying the dynamic–ecological approach in youth soccer to enhance motor performance abilities. While prior studies have suggested the benefits of this approach in motor learning across various sports [ 37 , 38 ], there is limited literature regarding its effects on motor skill development and exercise intensity [ 34 ]. This study is the first attempt to understand the relationship between dynamic–ecological methods and physical performance factors in young soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we have re-imagined specialised skill adaption processes elite coach development in sport. We considered it as a deeply entwined relationship between the developmental process of opening up and maintaining diversity of experience, integrated with a clarity of focus on succeeding in sport competition (for detailed arguments on performance specialisation in athletes, see Richard et al, 2023). This dualist perspective, currently popularised in high-performance sport systems, eschews a compliance with reductionist tenets on separating coaching for competitive performance and development of athletes and teams.…”
Section: Concluding Remarks and Outlook To Part IImentioning
confidence: 99%